THE IMPACT OF SOCIAL MEDIA PROPAGANDA IN POLITICS IN INDONESIA 2024 - Syahputra, Abdillah Nugraha; Lubis, Muya Syaroh Iwanda (Universitas Dharmawangsa Medan, 2024)
Social media has now become a platform for individuals to communicate with each other around the world, exchange ideas and voice their opinions on various topics. Propaganda illustrates the consequences of social media after World War I. Propaganda combined with social media would have a tremendous effect. Social media has had a significant impact on the way the public and netizens view the weaknesses of current government initiatives. This research aims to gain a deeper understanding of social phenomena by using qualitative methodology to understand them holistically. The influence of social media on Indonesian politics is the main topic of this research.